Anthelmintic Activities of Roots of Cocos nucifera and Aerial Parts of Jasminum multiflorum - PAL, DILIPKUMAR; KUMAR PAHARI, SANDIP; KUMAR MISHRA, ABHISHEK (Asian Journal of Chemistry, 2010)
The anthelmintic activities of different extract of roots of Cocos nucifera and aerial parts of Jasminum multiflorum were evaluated separately on adult Indian earthworm (Pheretima posthuma) and the activities were compared with standard drug piperazine citrate and albendazole. It was found that petroleum ether, benzene, chloroform and ethyl acetate extract of Cocos nucifera (PECN, BCN, CCN and EACN, respectively) and petroleum ether extract of Jasminum multiflorum (PEJM) exhibited dose dependant action and inhibition of spontaneous motility (paralysis) and death of earthworms. The results indicated that the PECN, BCN and CCN were more potent than EACN and PEJM.